Le Procès des poètes : Flaubert contre « l’écume du cœur » - Aurélie Loiseleur (Flaubert: Revue Critique et Génétique)
In Flaubert’s correspondence poets are rarely his principal addressees, yet they are his main target. Indeed, his letters, specially those written to the poet Louise Colet, give him the opportunity to re-examine his esthetical-sentimental creed and specify his own position as a prose poet in an open war against those who represent “the poetry of the heart”.